Piloting creative engagement strategies to explore themes of parenthood with fathers - Culpin, Iryna; Lamont-Robinson, Catherine; Billington, Mark; James, Matthew; Prewett, James; Ward, Gareth; Bes Garcia, Mireia; Biglino, Giovanni (Frontiers in Child and Adolescent Psychiatry, 2024)
Data Availability Statement: ALSPAC data are available through a system of managed open access. The study website contains details of all the data that is available through a fully searchable data dictionary and variable search tool data dictionary. The application steps for ALSPAC data access are highlighted below.1. Please read the ALSPAC access policy, which describes the process of accessing the data in detail, and outlines the costs associated with doing so.2. You may also find it useful to browse the fully searchable research proposals database, which lists all research projects that have been approved since April 2011.Committee. You will receive a response within 10 working days to advise you whether your proposal has been approved.